2008
DOI: 10.1056/nejmoa066886
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept Treatment for Children and Adolescents with Plaque Psoriasis

Abstract: Etanercept significantly reduced disease severity in children and adolescents with moderate-to-severe plaque psoriasis. (ClinicalTrials.gov number, NCT00078819 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
300
2
24

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 358 publications
(337 citation statements)
references
References 24 publications
11
300
2
24
Order By: Relevance
“…Durante el primer ensayo clínico en niños y adolescentes con psoriasis en placas moderada-grave, no se notificaron casos de muerte, cán-cer, infecciones oportunistas, tuberculosis (TB) ni enfermedades desmielinizantes 5,6 . En adultos, ha demostrado el mismo perfil de seguridad favorable en tratamientos de hasta 4,2 años 7,9-11,17,26,27 .…”
Section: Datos De Seguridad De Los Tratamientos Biológicosunclassified
“…Durante el primer ensayo clínico en niños y adolescentes con psoriasis en placas moderada-grave, no se notificaron casos de muerte, cán-cer, infecciones oportunistas, tuberculosis (TB) ni enfermedades desmielinizantes 5,6 . En adultos, ha demostrado el mismo perfil de seguridad favorable en tratamientos de hasta 4,2 años 7,9-11,17,26,27 .…”
Section: Datos De Seguridad De Los Tratamientos Biológicosunclassified
“…The effects of etanercept remained constant during the 24 weeks open label phase, whereas PASI values in the original placebo group gradually approached those in the etanercept group during these 24 weeks. A gradual loss of efficacy was seen in the placebo group during the second double-blind phase, whereas PASI-75 was reached in 75% of patients in the etanercept group [29].…”
Section: Efficacy Etanerceptmentioning
confidence: 99%
“…Regarding long-term efficacy, etanercept response has been demonstrated to last up to 96 weeks, resulting in a statistically significant improvement (Tyring et al, 2007;Esposito et al, 2010). Etanercept is the only biological drug that has shown efficacy and safety in pediatric patients with moderate to severe plaque psoriasis (Paller et al, 2008). Paller et al reported a PASI 75 response in 57% of children and adolescents treated with etanercept (0.8 mg/kg body weight) compared with 11% in placebo patients after 12 weeks.…”
Section: Clinical Efficacymentioning
confidence: 99%